BASICS OF ECOLOGICAL TERMINOLOGY: PREREQUISITES, RELEVANCE, IMPLEMENTATION (Ecological Bulletin of Kryvyi Rih District, 2021)
Ukraine’s integration into the world educational space, alongwith preserving the positive and effective achievements and traditions ofthe national model of education, aims to create new opportunities forforming their own life trajectory, the formulas for success of each individualcapable of self-education, self-awareness, self-determination, self-realizationand self-development. Nowadays, knowledge and education are becomingnot only factors of social development, but also its foundation and themost valuable way, catalyst for the formation of modern national elite.Phenomena and trends of current human development determine the relevanceof research aimed at substantiating and analyzing the prerequisites, relevance,implementation of the discipline “Basics of Ecological Terminology” in thetraining of ecologist based on the essence, meaning, terminological competenceas part of professionalism and ecological culture of national elite.The national elite determines the intellectual, moral and ethical, political,economic climate of society and is it’s most valuable capital and priorityresource. The decisive role in its preparation belongs to education, which is ableto form such personal qualities that contribute to the support of a sustainablesociety and the fulfillment of its development with innovative elements.An integral part of professional competence, professionalism is terminologicalcompetence, which can also be considered as an independent or as a structuralcomponent of information, communication, speech, culture. The study of itsessence, specifics, characteristics, levels of formation and analysis of relatedconcepts “terminology”, “terminology system”, “term” allow to identify currentproblems of terminological competence in ecological science related to thelevel of terminological potential of the individual, ecological culture, negativeaspects of modern process of term formation, problems of development ofecological terminology system. Formation of terminological competence of theecologist — systematic, optimally organized, purposeful, provided with the useof effective teaching aids and methods and concretized by its specific principles,focused on achieving the main objectives and goals of education, improvingecological culture and strengthening the professional elite, implementationof innovative activities and implementation of ecological imperatives in thedevelopment of the country.A component of the implementation of tasks and solving problems of formationof terminological competence of future highly qualified competitive ecologistscan be considered the introduction of the educational discipline “Basicsof Ecological Terminology” in educational programs of higher educationinstitutions, identification of aspects of term formation and term use, studyof the dynamics of terms and the role of the latter in professional knowledge,scientific, expert, industrial, managerial, innovative activities of the ecologist.
Keywords: ecology; elite; competence; term; terminology; terminology system; basics of ecological terminology